Legislated Ethics or Ethics Education?: Faculty Views in the Post-Enron Era - Beggs, Jeri Mullins (Journal of business ethics, 2007)
The tension between external forces for better ethics in organizations, represented by legislation such as the Sarbanes–Oxley Act (SOX), and the call for internal forces represented by increased educational coverage, has never been as apparent. This study examines business school faculty attitudes about recent corporate ethics lapses, including opinions about root causes, potential solutions, and ethics coverage in their courses. In assessing root causes, faculty point to a failure of systems such as legal/professional and management (external) and declining personal values (internal). We also found that faculty recommend external forces as a remedy more often than increased ethics educational coverage; we contextualize this finding with recent ethics education literature. We conclude by proposing that neither legislation nor ethics education alone are complete when addressing widespread unethical corporate acts and offer a multi-faceted approach to ethics educational opportunities.